Transanal irrigation (TAI) in the paediatric population: Literature review and consensus of an Italian multicentre working group - Enrica Caponcelli; Milena Meroni; Giulia Brisighelli; Claudia Rendeli; Emanuele Ausili; Piergiorgio Gamba; Antonio Marte; Barbara Daniela Iacobelli; Laura Lombardi; Ernesto Leva; Paola Midrio (PAGEPress Publications, 2021)
Constipation and fecal incontinence in pediatric patients are conditions due to either functional or organic bowel dysfunction and may represent a challenging situation both for parents, pediatricians, and pediatric surgeons. Different treatments have been proposed throughout the past decades with partial and alternant results and, among all proposed techniques, in the adult population the Transanal Irrigation (TAI) has become popular. However, little is known about its efficacy in children. Therefore, a group of Italian pediatric surgeons from different centers, all experts in bowel management, performed a literature review and discussed the best-practice for the use of TAI in the pediatric population. This article suggests some tips, such as the careful patients' selection, a structured training with expert in pediatric colorectal diseases, and a continuous follow-up, that are considered crucial for the full success of treatment.